2012
DOI: 10.1136/thoraxjnl-2012-202678.007
|View full text |Cite
|
Sign up to set email alerts
|

S1 High Levels of Latent TB Infection, Blood Borne Viruses and Unmet Need Among Hard to Reach Groups in London: The TB Reach Study

Abstract: A4Thorax 2012;67(Suppl 2):A1-A204cosmopolitan urban settings where human populations of different ancestry intermingle. These different strains induce distinct patterns of cytokine and chemokine secretion ('inflammatory profiles') in human macrophages. Circulating and antigen-stimulated inflammatory profiles might therefore be expected to vary significantly between tuberculosis patients of different ethnic origin. We therefore conducted a study to determine whether such variation exists. Background Urban homel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A recent clinical trial with the most promising CFTR corrector, VX-809 (Van Goor et al, 2011), in F508del-CFTR homozygous patients demonstrated modest dose-dependent reductions in sweat chloride (Clancy et al, 2012). However, beyond this laboratory parameter, no improvement in lung function or CF complications was reported (Clancy et al, 2012; Elborn, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent clinical trial with the most promising CFTR corrector, VX-809 (Van Goor et al, 2011), in F508del-CFTR homozygous patients demonstrated modest dose-dependent reductions in sweat chloride (Clancy et al, 2012). However, beyond this laboratory parameter, no improvement in lung function or CF complications was reported (Clancy et al, 2012; Elborn, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, combining CFTR correctors and potentiators may be a suitable approach for F508del-CFTR patients, provided that the corrector molecules are effective in increasing F508del-CFTR PM stability after rescue. Currently, phase II clinical studies evaluating the combination of VX-809 and the potentiator VX-770 in CF patients that express F508del-CFTR are underway (Elborn, 2012). …”
Section: Introductionmentioning
confidence: 99%